The influence of media channels on the destinations of the Iraqi citizen, an exploratory study of a sample of the provinces - Al-Katib, Faris Ibrahim (Al-Adab Journal, 2015)
The media organization in general and satellite channels in particular one of the key areas affecting public opinion, particularly with regard to the Iraqi issue, and inseparable for two reasons, first is that satellite television is one of the most important means of mass communication at all, especially political him. This as well as the role of educational and awareness and civilization. Second is the nature of the critical and very delicate stage through which Iraq for more than since the fall of the former regime and so far, and of the status of the US occupation and the successor of serious repercussions, including various aspects of Iraqi life, whether political or social, cultural or civilizational or other not only in their present but In the future choices as well. So study aims to shed light on how it would affect media channels in the orientation of the Iraqi citizen, the study confirmed the impact of the Iraqi channels on the orientations of the Iraqi citizen, because of its active role in the sound and image to convince him